Multiprobe molecular imaging of an NMDA receptor hypofunction rat model for glutamatergic dysfunction. (28th February 2016) - Kosten, Lauren; Verhaeghe, Jeroen; Verkerk, Robert; Thomae, David; De Picker, Livia; wyffels, Leonie; Van Eetveldt, Annemie; Dedeurwaerdere, Stefanie; Stroobants, Sigrid; Staelens, Steven
Abstract: There are many indications of a connection between abnormal glutamate transmission through N-methyl-d -aspartate (NMDA) receptor hypofunction and the occurrence of schizophrenia. The importance of metabotropic glutamate receptor subtype 5 (mGluR5) became generally recognized due to its physical link through anchor proteins with NMDAR. Neuroinflammation as well as the kynurenine (tryptophan catabolite; TRYCAT) pathway are equally considered as major contributors to the pathology. We aimed to investigate this interplay between glutamate release, neuronal activation and inflammatory markers, by using small-animal positron emission tomography (PET) in a rat model known to induce schizophrenia-like symptoms. Daily intraperitoneal injection of MK801 or saline were administered to induce the model together with N-Acetyl-cysteine (NAc) or saline as the treatment in 24 male Sprague Dawley rats for one month. Biweekly in vivo [ 11 C]-ABP688 microPET was performed together with mGluR5 immunohistochemistry. Simultaneously, weekly in vivo [ 18 F]-FDG microPET imaging data for glucose metabolism was acquired and microglial activation was investigated with biweekly in vivo [ 18 F]-PBR111 scans versus OX42 immunohistochemistry. Finally, plasma samples were analyzed for TRYCAT metabolites. We show that chronic MK801 administration (and thus elevated endogenous glutamate) causes significant tissue loss in rat brain, enhances neuroinflammatory pathways and may upregulate mGluR5 expression. Highlights: The first longitudinal multiprobe μPET study in a NMDAR hypofunction rat model. Chronic high glutamate tends to upregulate mGluR5 expression or shift the affinity. Microglial activation appears to amplify already increased glutamate levels. TRYCAT pathway overactivation contributes to the pathology. Targeting mGluR5 receptors for antipsychotics development remains promising.